2004
DOI: 10.1111/j.0953-816x.2004.03415.x
|View full text |Cite
|
Sign up to set email alerts
|

The LIM homeobox gene, L3/Lhx8, is necessary for proper development of basal forebrain cholinergic neurons

Abstract: Basal forebrain cholinergic neurons (BFCNs) are involved in cognitive functions such as learning and memory, and are affected in several neurodegenerative diseases (e.g. Alzheimer's disease). Despite their importance, the molecular mechanisms of their development are not fully elucidated. A recent report demonstrated that some BFCNs in adult rat are positive for L3/Lhx8, a LIM homeobox transcription factor. To examine the function of L3/Lhx8 in the development of BFCNs, we generated L3/Lhx8 gene-disrupted mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
3
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 42 publications
4
92
3
5
Order By: Relevance
“…Interestingly, reduction of CSIs was associated with increased number of Lhx6-expressing striatal interneurons (Fig. S1F), a characteristic feature of Lhx7-null mice (8,(12)(13)(14). Therefore, upon Cre-mediated recombination, Lhx7 fl is converted into a null allele.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Interestingly, reduction of CSIs was associated with increased number of Lhx6-expressing striatal interneurons (Fig. S1F), a characteristic feature of Lhx7-null mice (8,(12)(13)(14). Therefore, upon Cre-mediated recombination, Lhx7 fl is converted into a null allele.…”
Section: Resultsmentioning
confidence: 94%
“…"Terminal selector genes" encode transcription factors that coordinately regulate the expression of diverse molecular, morphological and functional characteristics that constitute the terminal phenotype of neurons (23). Lhx7 and Lhx6 belong to this class of genes because, respectively, they regulate multiple aspects of cholinergic and GABAergic interneuron differentiation in the mammalian forebrain (8,10,(12)(13)(14). In vertebrates terminal selector genes have been studied mostly in the context of lineage restriction and forward neuronal differentiation, but their subsequent role in maintaining neuronal subtype identity is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the basics of a cholinergic transcription factor code are emerging. A variety of experimental approaches has demonstrated that expression of several transcription factors is important (Mash 1, Olig2, Lmx7, Lmx8) or essential (Nkx2.1) for generating forebrain cholinergic neurons (Bachy and Retaux, 2006;Furusho et al, 2006;Marin et al, 2000;Mori et al, 2004;Zhao et al, 2003). Thus, the combined expression of these factors, and their target genes, probably accounts for much of the intrinsic identity of the cholinergic phenotype.…”
Section: A Development Of Cholinergic Systemsmentioning
confidence: 99%